Pelatihan Dan Perwantan AC Di Pesantren Tahfidz Markaz Hadits Bilal Bin Rabah - Sunardi; Woro Agus Nurtiyanto; Angga Septian MN; Rijal Aditya R; Andriyansah; Aditya Alkahfi; Rizal Ardiansyah; Imam Assidiq (CV. Multi Kreasi Media, 2024)
Today's Air Conditioner (AC) cooling systems are included in the basic needs category, especially for tropical climate areas such as Jakarta and its surroundings and many other areas in Indonesia. The use of air conditioning provides many benefits for human life, namely providing comfort during work or study activities and resting, thereby increasing productivity and maintaining the health of the human body, especially for students and educators at the Tahfidz Markaz Hadits Bilal Bin Rabah Islamic Boarding School. One type of AC cooler that is often used by people is the split wall (non-inverter) AC type because it has several advantages, including cheaper prices and fairly easy installation. Like most other electronic products, ACs must also undergo regular maintenance, according to product guidelines and usage time, so that the AC can work optimally without problems and extend the lifespan of the AC. To carry out maintenance independently and equip the students with knowledge and expertise, Pamulang University lecturers and students in the electrical engineering study program carry out one of the tri dharmas of higher education, namely community service with the title